Comparison of Different Volumes of Local Anaesthetic to Determine Optimal Volume to Be Used In TAP Block For Post Caesarean Section Analgesia - Shraddha Malik; Sunny Malik; Wahaja Karim; Reena Chabda (Academia Anesthesiologica International, 2019)
Background: The transverse abdominis plane (TAP) block, provides effective analgesia after lower abdominal surgeries if used as part of multimodal analgesia. In this prospective, randomized double-blind study, we proposed to determine the optimal volume of local anaesthetic to be used in ultrasound guided TAP (transversusabdominis plane) block for post Caesarean section analgesia.Subjects and Methods:Total 90 parturients were randomly allocated to group A, group B and group C to receive after routine spinal anaesthesia, bilateral TAP blocks with 15ml, 20ml and 30 ml of 0.2% Ropivacaine in addition to standard analgesic comprising intravenous(IV) Acetaminophen, 1 gram 8 hourly and IV patient-controlled analgesia (PCA) with fentanyl. Each patient was assessed at 0.5, 2, 4, 6, 8, 10, 12, and 24 hours after surgery by an independent observer for pain at rest and on movement using visual analog scale, time of 1st demand for fentanyl, total consumption of PCA fentanyl, satisfaction with pain management and side effects(nausea , vomitng and sedation).Results:Use of fentanyl was significantly reduced in group B and C compared to Group A during 24 h after surgery (P < 0.001). Pain scores were lower both on rest and activity at each time point for 24 h in groups B and C (P < 0.001), time of first analgesia was significantly longer, satisfaction was higher, and side effects were less in group B and C compared to group A. The difference was not significant between group B and C.Conclusion: We concluded that though increasing the volume of local anaesthetic from 15 ml bilaterally to 20 ml bilaterally resulted in increased duration and quality of analgesia, further increase to 30 ml bilaterally offered no significant advantage in terms of reduction in VAS scores or opioid consumption.